ENHANCING STUDENTS PROFICIENCY in WRITING EXPOSITION PARAGRAPH THROUGH COLLABORATION - Umi Sholihah; Ana Setyandari (Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2019)
This study aims at enhancing students’ writing exposition paragraph through collaboration by utilizing Google Docs and peer-review technique. Based on the findings in preliminary research, students got difficulties in writing. The subject of this research is the fourth semester students of English Study Program of Widya Dharma University Klaten. Data showed from the pre-test, the students’ skills in each writing aspects are still low, namely organization (62%), content (65%), syntax/grammar (61%), mechanics (57%), and vocabulary (66%). The techniques of collecting the data in this study are observation, interview, questionnaire, and test. The technique of analyzing the data is using interactive model analysis from Miles & Huberman for qualitative data and descriptive statistic for quantitative data. The results of the study show that there are significant improvement of students’ writing exposition paragraph viewed from mean scores of pre-test (63, 1), cycle I (68, 35), cycle II (73, 2), and cycle III (81, 55). The findings also present that teaching writing through collaboration by using peer review technique using Google Docs can improve the students’ analytical and critical thinking, self-confidence, and social relation; make students to be more active; and create meaningful learning of the class situation.